Comprehensive Genetic analysis of linear type traits characterized the Sahiwal cattle in an Organized Herd - Mukherjee, Sabyasachi; Pandey, Divyanshu; Mukherjee, Anupama; Gowane, Gopal; Kamboj, M L; Lathwal, S S; Malhotra, Ravinder; Rathee, Satish Kumar (Indian Journal of Dairy Science, 2023)
Background: Sahiwal is one of the most important dairy cattle breeds of the Indian subcontinent. A holistic and balanced approach to selection and breeding strategies must be adopted to bring about desirable genetic improvement in livestock, including indigenous cattle. The inclusion of linear type traits for dairy cattle selection in any breed improvement programme has not been carried out in our country so far. Therefore, this study was taken up to analyze and characterize Sahiwal cattle, on the basis of linear type traits.Methods: Linear type data were recorded on adult Sahiwal cows (N=185) up to their 10th parity, from the Institute herd of ICAR-National Dairy Research Institute, Karnal, Haryana, India. Production data during the years 2006-2018 were collected from the record section of the AGB Division and were analysed using Least Squares Maximum Likelihood (LSMLMW), considering a sire model for the present study. Parity, season and period of calving were taken as fixed effect and age at first calving as covariable. Sire or animal was considered as random variable.Results: Least squares means of objective linear type traits viz., stature was 125.97±0.68 cm, body length 136.58±1.01 cm, chest girth 173.04±1.14 cm, body depth 203.40± 1.39 cm, rump angle 14.50±0.39 cm, rump width 20.62±0.28 cm, udder depth 20.87±0.41 cm, rear udder height 18.38±0.33 cm, and teat length 6.16±0.24 cm. On the other hand, least square mean scores of subjective linear type traits (1-9 scale) viz. fore teat placement was 6.32±0.46, rear teat placement was 7.27±0.35, rear leg side view was 6.26±0.26, rear leg rear view was 6.28±0.27 score, foot angle 6.86±0.27, angularity 34.97±0.50-degree, central ligament 6.55± 0.39, fore udder attachment 5.91±0.32, fore teat placement 6.32±0.46, and rear teat placement was 7.27±0.35. Parity had a significant (p